KAJIAN PENGEMBANGAN POTENSI PARIWISATA KAWASAN PESISIR PANTAI KABUPATEN ACEH TIMUR - Andini Risfandini (Jurnal Pariwisata Pesona, 2019)
The aim of this research is to search for the potensial of the tourism development in East Aceh Regency based on the concept of sustainable tourism develepment. This research is using qualitative approach to identify the appropriate pattern for tourism development in coastal area in East Aceh Regency. Based from this research, it can be concluded that education for the local people to change their way of thinking on tourism is very important. The support from the local people is essential for the planning of sustainable tourism development. Sense of belonging for the culture and tourism will promote proudness and will get the local people to participate in tourism development in their area.